Genetic or pharmacological GHSR blockade has sexually dimorphic effects in rodents on a high-fat diet - Lékó, András H. (2024)
The stomach-derived hormone ghrelin regulates essential physiological functions. The ghrelin receptor (GHSR) has ligand-independent actions; therefore, GHSR gene deletion may be a reasonable approach to investigate the role of this system in feeding behaviors and diet-induced obesity (DIO). Here, we investigate the effects of a long-term (12-month) high-fat (HFD) versus regular diet on obesity-related measures in global GHSR-KO and wild-type (WT) Wistar male and female rats. Our main findings are that the GHSR gene deletion protects against DIO and decreases food intake during HFD in male but not in female rats. GHSR gene deletion increases thermogenesis and brain glucose uptake in male rats and modifies the effects of HFD on brain glucose metabolism in a sex-specific manner, as assessed with small animal positron emission tomography. We use RNA-sequencing to show that GHSR-KO rats have upregulated expression of genes responsible for fat oxidation in brown adipose tissue. Central administration of a novel GHSR inverse agonist, PF-5190457, attenuates ghrelin-induced food intake, but only in male, not in female mice. HFD-induced binge-like eating is reduced by inverse agonism in both sexes. Our results support GHSR as a promising target for new pharmacotherapies for obesity.